Foreign Presence and Indonesian Food Industry Performance - Nauly, Dahlia; Harianto, Harianto; Hartoyo, Sri; Novianti, Tanti (International Journal of Economics and Financial Issues, 2020)
This paper analyzes the influence of foreign presence on the performance of food industry in Indonesia using panel data from 28 subsectors in the period of 2011-2015. The data used is the Annual Survey of Large and Medium Industries (IBS) from Statistics Indonesia. The performance indicator utilized is the price cost margin (PCM). The PCM model was estimated using regression and tested with the Hausman statistical test. The results show that foreign presence increases the performance of Indonesia's food industry. Other factors that affect the industry's performance are industry concentration, market growth and imports of raw materials. Foreign presence, concentration and market growth have a positive effect on performance, meanwhile import ratio has a negative effect. The government needs to continue to encourage foreign investment in the food industry since the presence of foreign presence will improve industrial performance. In addition, efforts are also needed to supply quality raw materials by encouraging the development of domestic upstream industries. Keywords: foreign presence, margins, food industry, Indonesia JEL Classifications: L25, L66 DOI: https://doi.org/10.32479/ijefi.9140